Penerapan Hasil Analisis Tindakan Pemberontakan Residen Napza Medan Plus Menggunakan Cognitive Behavior Therapy (CBT) - Tasya Uli Marsuara Manurung; Anita Maisaroh; Yolanda Oktari Br Bangun; Mario Delo; Arnold Munthe (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
The research conducted by the members of this group aims to analyze the problems that exist in a Medan Plus Rehabilitation Center. Group members write and record how the activities of the residents of the orphanage fulfill their social functions while in rehabilitation. This writing explains one of the causes of the problem of rebellion experienced by the residents while in the central rehabilitation center. In this study, the authors used a qualitative research method, namely interviews conducted with professional social workers, managers and staff at the orphanage. As for the results obtained from the analysis of this case, it was found that one of the causes of the rebellion by the residents was the inability to be able to place himself in the orphanage because of the rules and even strict supervision of the residents. So, there was an uprising to escape from that place, therefore the results of this research were obtained by a solution from the author, namely by incorporating a therapy from psychology, namely Cognitive Behavior Therapy (CBT) which is one of the individual counseling cognitive therapies that focuses on individual problems. , this therapy was taken because the authors focused on residents who rebelled to conduct closed interviews by using several questions to find out the causes of the actions taken by residents during rehabilitation